Produção e eficiência nutricional de cultivares de cenoura sob adubação fosfatada - Jesus, Priscila Maylana Modesto de (2018)
The carrot is one of the vegetables with great economic expression in the country. In this crop, phosphate fertilization is considered a key component because it contributes to root formation and post-harvest quality maintenance. The objective of this research was to evaluate the production and nutritional efficiency of carrot cultivars under phosphate fertilization, due to the large quantities applied in the planting for higher yields, in addition to being one of the most expensive of production. The experiments were carried out from July to November of 2016 and from June to October of 2017, at the Experimental Farm Rafael Fernandes, Alagoinha district, Mossoró, RN. The experimental design was in randomized blocks, in a 4x4 factorial scheme with 4 replicates, combined among the cultivars (Brasília, Planalto, Suprema and Nativa) with the doses (0, 90, 180 and 270 kg ha-1 P2O5). The characteristics analyzed were: Root classification; Commercial productivity; Non-commercial productivity; Total Productivity; Dry leaf mass, roots and plant; P content in the diagnostic leaf and classification of the cultivars regarding the efficiency and response to phosphate fertilization. In general, the use of phosphorus provided an increase in plant height and dry matter of leaves, roots and total, as well as in the production of medium and long roots for all cultivars. The doses that maximized the commercial productivities were 186,8; 208,0; 217,6 and 243,5 kg ha-1 of P2O5 for the Native, Supreme, Plateau and Brasília cultivars, respectively. The native cultivar was the most efficient and responsive, while Brasília and Plateau were not efficient and not responsive to the use and application of phosphorus